2020
DOI: 10.1002/advs.202002488
|View full text |Cite
|
Sign up to set email alerts
|

van der Waals Magnets: Material Family, Detection and Modulation of Magnetism, and Perspective in Spintronics

Abstract: van der Waals (vdW) materials exhibit great potential in spintronics, arising from their excellent spin transportation, large spin–orbit coupling, and high‐quality interfaces. The recent discovery of intrinsic vdW antiferromagnets and ferromagnets has laid the foundation for the construction of all‐vdW spintronic devices, and enables the study of low‐dimensional magnetism, which is of both technical and scientific significance. In this review, several representative families of vdW magnets are introduced, foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 187 publications
(452 reference statements)
1
46
0
Order By: Relevance
“…For instance, Huang et al reported extraordinarily large magneto-optical Raman effects of A1g phonon 2D magnet CrI3 due to spin-phonon coupling (Fig. 13d, e) 440,441 . Deep insights are needed on the observation of forbidden Raman modes, including new edge modes related to electromagnetic field distortion of incident and scattered light 442 , acoustic phonons under double-resonance excitation 443 and cross-dimensional electron-phonon coupling between 3D phonons and 2D excitons 444 .…”
Section: Raman Scatteringmentioning
confidence: 99%
“…For instance, Huang et al reported extraordinarily large magneto-optical Raman effects of A1g phonon 2D magnet CrI3 due to spin-phonon coupling (Fig. 13d, e) 440,441 . Deep insights are needed on the observation of forbidden Raman modes, including new edge modes related to electromagnetic field distortion of incident and scattered light 442 , acoustic phonons under double-resonance excitation 443 and cross-dimensional electron-phonon coupling between 3D phonons and 2D excitons 444 .…”
Section: Raman Scatteringmentioning
confidence: 99%
“…[8] The discovery of 2D van der Waals (vdW) magnetic materials provides an excellent platform for the study of the exchange bias effect. [9,10] Since the intrinsic AFM order in FePS 3 and the FM order in CrGeTe 3 were reported, [11,12] the family of 2D vdW magnetic materials has been rapidly enriched. [13][14][15][16][17][18][19][20] Similar to other 2D vdW materials, the layers in a vdW magnetic material are connected by vdW interaction, which will produce a perfect surface without dangling bonds.…”
Section: Introductionmentioning
confidence: 99%
“…They can be stacked with other vdW materials to rationally create various 2D heterostructures with designed degrees of strain, optical and electrical properties. [1][2][3][4][5][6][7][8][9][10] Moreover, the magnetism of vdW magnets can be effectively controlled by magnetic field, electric field, [11,12] interfacial symmetry, [13] pressure, [14,15] and doping. [16] In order to further miniaturize the device, the fabrication of vdW magnets of only a single or few layers has been long pursuit.…”
Section: Introductionmentioning
confidence: 99%